The Limits of Political Compromise: Debt Ceilings and Political Turnover - Alexandre B. Cunha; Emanuel Ornelas (Center for Economic Studies and ifo Institute (CESifo), 2017)
We study the desirability of limits on the public debt and of political turnover in an economy where incumbents have an incentive to set public expenditures above the socially optimal level due to rent-seeking motives. Parties alternate in office and cannot commit to future policies, but they can forge a political compromise where each party curbs excessive spending when in office if it expects future governments to do the same. In contrast to the received literature, we find that strict limits on government borrowing can exacerbate political economy distortions by making a political compromise unsustainable. This tends to happen when political turnover is limited. Conversely, a tight limit on the public debt fosters a compromise that yields the efficient outcome if political turnover is vigorous. Our analysis thus suggests that to sustain good economic policies, a society needs to restrict either the extent of political turnover or the ability of governments to issue debt, but not both.
Keywords: E61; E62; H30; H63; 330; debt limits; political turnover; efficient policies; fiscal rules